Efficient data compression scheme based on semi-adaptive Huffman coding for moderately large Chinese text files - Ong, Ghim Hwee (2014)
Proceedings of IEEE Singapore International Conference on Networks/International Conference on Information Engineering IEEE SICON/ICIE